A RECORD OF AN UNUSUALLY LARGE TIGERSHARK, CALEOCERDO ARTICUS (FABR.), FROM OFF VERA - Kasim, H Mohamad; Khan, Mohammad Zafar (Indian Journal of Fisheries, 2011)
An unusually big specimen of a Tiger shark, Galeocerdo articus (Fabr.),measuring 378 cm is recorded from Veraval, and a brief description of the specimenis given